Myosin-V Induces Cargo Immobilization and Clustering at the Axon Initial Segment - Janssen, Anne F. J.; Tas, Roderick P.; van Bergeijk, Petra; Oost, Rosalie; Hoogenraad, Casper C.; Kapitein, Lukas C. (Frontiers in Cellular Neuroscience, 2017)
The selective transport of different cargoes into axons and dendrites underlies the polarized organization of the neuron. Although it has become clear that the combined activity of different motors determines the destination and selectivity of transport, little is known about the mechanistic details of motor cooperation. For example, the exact role of myosin-V in opposing microtubule-based axon entries has remained unclear. Here we use two orthogonal chemically-induced heterodimerization systems to independently recruit different motors to cargoes. We find that recruiting myosin-V to kinesin-propelled cargoes at approximately equal numbers is sufficient to stall motility. Kinesin-driven cargoes entering the axon were arrested in the axon initial segment (AIS) upon myosin-V recruitment and accumulated in distinct actin-rich hotspots. Importantly, unlike proposed previously, myosin-V did not return these cargoes to the cell body, suggesting that additional mechanism are required to establish cargo retrieval from the AIS.